Triazole-Extended Anthracenes as Optical Force Probes - Baumann, Christoph; Göstl, Robert (Synlett, 2021)
Optical force probes (OFPs) are force-responsive molecules that report on mechanically induced transformations by the alteration of their optical properties. Yet, their modular design and incorporation into polymer architectures at desired positions is challenging. Here we report triazole-extended anthracene OFPs that combine two modular ‘click’ reactions in their synthesis potentially allowing their incorporation at desirable positions in complex polymer materials. Importantly, these retain the excellent optical properties of their parent 9-π-extended anthracene OFP counterparts.
Keywords: mechanochemistry; fluorescence; polymers; cycloaddition; chromophores